SISTEM NILAI DAN HUBUNGANNYA DENGAN PROSES PENDIDIDKAN ISLAM - ., Rustam (Inspiratif Pendidikan, 2018)
This journal deals with research studies on the value system and its relationship in the process of Islamic education (Axiology Study of Islamic Education). The main problem is how the value system relates to the process of Islamic education and the degree to which the value system relates to the process of Islamic education. This problem is seen with a pedagogical approach and discussed with library research methods, processed by inductive, deductive and comparative methods. Writing this journal intends to find out how the system of values and relationships in the process of Islamic education. The results of the writing indicate that the value system is very important, moreover this system is elements that are regularly and interrelated with the values caused by the subject. The relationship with the Islamic teaching process is very close to value, so it has a reciprocal relationship, meaning the subject with an object or in other words there is a cause for the emergence of everything. Values do not arise by themselves, but there are factors that are prerequisites. The realization of the value system in the process of Islamic education is not only used as a consultation material in the formulation of the objectives of Islamic education, but also a reference in education systems, strategies, and technology as well as educative interactions with the outside world and within Islamic educational institutions.